2014
DOI: 10.1021/ma500928p
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Stimuli-Responsive Poly(N-isopropylacrylamide) Hydrogel Layers As Revealed by Fluorescence Correlation Spectroscopy

Abstract: Experimental sectionFigure.S1. Normalized fluorescence intensity profile, I F (z)/I F,max , for A488 in HG-6 (white) and in the supernatant solution (grey) vs. distance z normal to the substrate (grey), at different ionic strength (I) values of a monovalent salt (KNO 3 ) , at 25°C. The grey highlighted regions denote the bounds of the fully swollen HG thickness at each I value.Interpretation of the z-scans: For the fitting procedure, we consider a gel grafted on a glass slide such that the glass-gel interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Interestingly, similar trend was observed for the amplitude of the slow molecular tracer diffusion in the same PNIPPAM hydrogel layers upon adding monovalent salt. The slow tracer diffusion is associated with a dynamic arrest in the dense (collapsed) domain …”
Section: Dynamic Structure Of Grafted Pnipaam Hydrogel Layers In the mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, similar trend was observed for the amplitude of the slow molecular tracer diffusion in the same PNIPPAM hydrogel layers upon adding monovalent salt. The slow tracer diffusion is associated with a dynamic arrest in the dense (collapsed) domain …”
Section: Dynamic Structure Of Grafted Pnipaam Hydrogel Layers In the mentioning
confidence: 99%
“…The slow tracer diffusion is associated with a dynamic arrest in the dense (collapsed) domain. [ 44 ]…”
Section: Dynamic Structure Of Grafted Pnipaam Hydrogel Layers In the mentioning
confidence: 99%
“…In consequence, many polymer systems (concentrated solutions, membranes, gels) deviate from normal (Fickian) diffusion. [1][2][3][4][5][6][7] Diffusion is an especially important issue in stimuli responsive gels exhibiting volume phase transition (VPT). In such systems, molecular mobility (diffusivity in the case of water and molecular relaxations of polymer segments) is one of the key factors that determine dynamics of VPT.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS) has been previously shown effective to measure in situ transport properties of small molecules in various polymeric systems . This includes the use of FCS to examine the diffusion of probe molecules in hydrogels . It has been shown that higher molar ratios of chemical crosslinkers lead to slower diffusion of probe molecules .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] This includes the use of FCS to examine the diffusion of probe molecules in hydrogels. [17,[25][26][27][28][29] It has been shown that higher molar ratios of chemical crosslinkers lead to slower diffusion of probe molecules. [30] Less studied are the effects of water content during hydrogel synthesis on the transport properties of probe molecules.…”
Section: Introductionmentioning
confidence: 99%